Analysis of Online Travel Agent Receivables Procedures with VHP Accounting Information Systems (Case Study at XYZ Hotel) - Aribah Drajat, Nabilah; Wijaya, Raden Muhammad Syah Arief Atmaja (Fakultas Ekonomika dan Bisnis Universitas PGRI Kanjuruhan Malang, 2024)
The rapid development of technology is being used well by various sectors, one of which is the hotel services sector in the operational activities of a company. At XYZ Hotels, an accounting information system in the VHP (Visual Hotel Program) is used for recording processes, making payments, and predicting income receivables from Online Travel Agent (OTA) to be well managed. Problems sometimes occur in the procedures for recording and payment of OTA receivables, so there needs to be a plain and standard procedure to serve as a guide. Therefore, this research explains the procedure of OTA receivables with the Accounting Information System VHP (case study at XYZ Hotel). This research was started in January until May 2024 to explain the procedures for OTA receivables with the Accounting Information System VHP (case study at XYZ Hotels). This research used qualitative research methods with data collection techniques using observation, interviews, library research, and documentation. The results of this research are that the procedure for recording and payment of OTA receivables using the VHP has been running well because the system supports it and the website of the OTA makes it easy to reconcile or match data.